Association of BDNF rs6265 polymorphism with Lithuanian elite athletes` status - Gineviciene, V.; Anikeviciute, G.; Sivaciova, M. O. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Regular physical activities lead to an increase in brain-derived neurotrophic factor (BDNF) and other myokines concentration level in the blood serum, which determines the general physical and psychological health of a person. BDNF (encoded by the BDNF gene) is present in the blood both at rest and during exercise training, and is derived from several tissue sources (such as skeletal muscle, brain, vascular endothelial cells, peripheral neurons, blood mononuclear cells, platelets etc.) known to produce and release neurotrophic factors into circulation in response to exercise. The single nucleotide polymorphism (SNP, rs6265, C>T, Val66Met) in the BDNF gene affect the intracellular distribution, packaging and release of BDNF protein, and can affect neuronal adaptation and response to exercise, as well as the ability to activate the appropriate muscles and generate more power. However, the influence of this SNP on the characteristics of elite athletes remains not clear. The purpose of this study was to investigate the relationship of the BDNF rs6265 genetic variant with elite Lithuanian athlete status.